SCALING CLOUD APPLICATIONS: FROM STARTUP TO ENTERPRISE - A TECHNICAL JOURNEY - Chakradhar Sunkesula (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This in-depth technical article examines how cloud applications have changed, moving from small-scale implementations to enterprise-class solutions. Microservices and containerization-based architectural foundations, performance optimization through sophisticated caching and database strategies, enterprise-grade security implementations, high availability and reliability measures, cost optimization strategies, customization and integration patterns, and other crucial elements of this transition are all examined. The article offers comprehensive advice on how businesses may effectively handle the difficulties of growing cloud apps without sacrificing cost, performance, or security. It provides a platform for businesses pursuing comparable scaling ambitions by analyzing current industry practices and new developments.